Interactions between Light and the Circadian Clock in the Regulation of CAT2 Expression in Arabidopsis. - Zhong, H. H. (1994)
In Arabidopsis seedlings germinated and grown in continuous light, CAT2 mRNA abundance peaks 1 d after imbibition, consistent with the role of catalase in detoxifying H2O2 generated during the [beta]-oxidation of fatty acids stored in the seed. A second peak of CAT2 mRNA abundance, of lower amplitude than the initial peak, appears 6 d after imbibition and may be associated with the development of photosynthetic competence and induction of photorespiration. This second peak in steady-state CAT2 mRNA abundance is regulated by light and is not seen in etiolated seedlings. CAT2 mRNA accumulation is induced by exposure to high-fluence blue or far-red light but not by red light. In addition, light induction is unaffected by several mutations that block blue light-mediated inhibition of hypocotyl elongation (blu1, blu2, blu3, hy4), suggesting phytochrome involvement. When etiolated seedlings are transferred to continuous white light, CAT2 mRNA rapidly (within 30 min) accumulates. It is interesting that in these seedlings CAT2 mRNA abundance undergoes pronounced oscillations with a circadian (24 h) periodicity, indicating control by the endogenous circadian clock. No such oscillations are detected in CAT2 mRNA abundance in etiolated seedlings prior to illumination. Control of CAT2 expression by the circadian clock is also seen in 5-week-old plants grown in a light-dark cycle and transferred either to continuous dark or to continuous light; in continuous light the circadian oscillations in CAT2 mRNA abundance persist for at least five circadian cycles, indicating the robustness of this circadian rhythm.